Utvecklingsalternativ för grisbesättning - Johansson, Christian (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
The purpose of this report was to compare two different options for expanding of an existing pig farm. For the time being there are low prices within the agricultural market of pig production, and it is interesting to see if it is worth expanding or not. The two different options this report is based on are: expanding from a herd with 50 sows in breeding gilt production to a herd with 100 sows in breeding gilt production (option 1), or expanding to a herd with 140 sows in breeding gilt production (option 2). The number of pregnant gilts produced per year will stay the same for both alternatives; about 300 pregnant gilts per year. The rest of the breeding gilts will be sold at a weight of 25 kg. The pigs that are not sold as breeding gilts (e.g. castrates, and female pigs that are too small or that have disorders) will be kept on the farm as growing-finishing pigs until 120 kg of live weight, and then sold to the slaughter house. By using the existing buildings, even after the expanding, the investment costs, and thereby costs for housing, were kept as low as possible. The economic result was 121, 435 SEK per year for an increase to 100 sows, and 85, 302 SEK per year for an increase to 140 sows. It was concluded that option 1 is the most appropriate choice economically. With option 1 there is no need to employ any more staff and less grain has to be bought for own feedstuff production as compared to option 2. Another advantage of option 1, as compared to option 2, is the lower demand of straw and the lower demand of land for spreading the manure.